Effect of mixing paddy straw with molasses and urea on fermentation characteristics and nutritive value of maize silage - GOYAL, MEENAKSHI; KAUR, RAMAN PREET; PAL, RAVI PRAKASH; SINGH, DEVINDER PAL (The Indian Journal of Animal Sciences, 2023)
The present investigation was aimed at studying the improvement of fermentation and nutritive quality of rice straw-maize silage by the inclusion of different additives. In the experiment, paddy straw and green maize fodder were mixed in ratios of 100:0, 75:25, 50:50, 25:75, and 0:100 for silage preparation. These combinations were made in a triplicate and added with no additive (C), 2% urea (T1), 1% molasses (T2) and a mixture of 2% urea and 1% molasses (T3) in completely randomized design (CRD). The silages were harvested after 45 days and then analyzed for chemical composition, fermentation characteristics and anti-nutritional factors. Results revealed that dry matter (DM), acid detergent fibre (ADF), neutral detergent fibre (NDF), crude fibre (CF), ash and pH increased with an increase in the proportion of paddy straw in all combinations. Addition of 2% urea increased in vitro dry matter digestibility (IVDMD), crude protein (CP) and total gas production (TGP) of paddy straw and maize fodder silage. Urea treatment considerably reduced the oxalate content and increased the tannin content of paddy straw and maize fodder silage. In the present study, silage prepared by combining paddy straw and maize fodder in ratio of 25:75 had good aroma and fermentation characteristics which can be, therefore, utilized for effective silage making.